What Determines Student Decision to Select Islamic Bank in Indonesia? - Bagus Eka Saputra; Edy Yusuf Agung Gunanto (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2020)
Indonesia has a very large muslim population. The large number of muslim population in Indonesia will certainly affect the behavior of consumers from the public to use Islamic banking services. This study aims to determine the effect of religiosity, income, service, promotion and location on the decision of students of the faculty of economics in Semarang to use Islamic banks. The population in this study were students of the faculty of economics in the city of Semarang. This research is quantitative study conducted by distributing questionnaires to 191 respondents with purposive random sampling method. This research uses multiple linier regression analysis which is processed using SPSS version 23. The study found that the factors of religiosity, promotion and location partially have a significant effect on the decision of students to select Islamic banks. While the income and service variables partially did not significantly influence the decision of students to use Islamic banks.